2018
DOI: 10.1002/jmr.2705
|View full text |Cite
|
Sign up to set email alerts
|

Study on the molecular recognition action of lamivudine by human serum albumin

Abstract: In this work, the interaction of an anti-HIV drug lamivudine and human serum albumin (HSA) was studied by multispectroscopic and molecular modeling methods. The fluorescence emission spectra showed that the fluorescence of HSA was quenched by lamivudine through static mechanism with HSA-lamivudine complex produced at ground state. According to the binding equilibriums observed at 4 different temperatures, the number of binding site, binding constant, enthalpy change, entropy change, and Gibbs free energy chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…In Figure , the significant red shift of λ max for the synchronous FLS of Δ λ at 60 nm (from 276 to 285 nm) and Δ λ at 15 nm (from 285 to 289 nm) suggested that these two residues had been transferred to more hydrophilic surroundings …”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…In Figure , the significant red shift of λ max for the synchronous FLS of Δ λ at 60 nm (from 276 to 285 nm) and Δ λ at 15 nm (from 285 to 289 nm) suggested that these two residues had been transferred to more hydrophilic surroundings …”
Section: Resultsmentioning
confidence: 97%
“…Fluorescence spectra (FLS) were detected using a Hitachi F‐4600 spectrofluorometer. Emission spectra were obtained when excitation energy was set at 285 nm and the data used to calculate these results were corrected in accordance with a published equation to diminish any inner filter effect. CD measurements were carried out at 296 K on a Japanese Jasco J‐810 spectropolarimeter using 1.0‐cm quartz cells and under a nitrogen atmosphere.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fluorescence measurements have been widely utilized to evaluate the interaction of proteins with small molecules. 29 The BLG protein contains three chromophores that can exhibit fluorescence: tyrosine (Tyr), tryptophan (Trp), and phenylalanine (Phe). These chromophores are sensitive to their environment.…”
Section: Intrinsic Fluorescence Quenching Of Blg In the Presence Of Azmmentioning
confidence: 99%
“…Similar thermodynamic data were found when BLG interacted with rhein; the enthalpy and entropy values were positive, indicating that hydrophobic forces were the dominant forces in this interaction. 29…”
Section: Calculation Of Thermodynamic Parameters and Identification O...mentioning
confidence: 99%